Pendampingan Penggunaan Internet Sehat di SD Negeri Mangasa Kota Makassar - MS, Sri Rahayu; Arizah, Ainun; Septiani, Elya (Jurnal Pengabdian kepada Masyarakat Nusantara, 2024)
The presence of Internet in society, has changed the way of life and the culture of mankind, whether it work, study, shopping, communicating and various other aspects of life. Nowadays, people prefer to communicate by the Internet, such as mailings, social networks and so on because it's considered more efficient and effective. Although the Internet provides access to a large amount of information and resources, it is important to be aware that not all content is suitable or safe for “young” users. Internet without supervision will have a negative impact on children's development. This article aims to see to what extent the child's understanding of the Internet and educate the participants will be the importance of having a healthy, secure Internet, as well as tips on using the Internet wisely. The methods used by forming a PKM group, preparation, implementation of the PKM, and monitoring and evaluation of PKM implementation. The activity was followed by 25 participants, namely students/students of SD State Mangasa. The identification results showed that the internet was used by the participants for school duties, playing games, watching videos, and social networks. The activities then continued with the playback of educational videos with the material of understanding the internet, devices that can be connected to the Internet, how the Internet works, the functions and benefits of the Internet, dangerous things in the use of the internet as well as the way to use the Internet good and correct.